Community health for nursing practice review module - Treas, Leslie Schaaf; Calbeck, Pam.; Assessment Technologies Institute (Overland Park, KS Assessment Technologies, 2005)
This review module is a component of the Comprehensive Assessment and Review Program and is designed to be used in conjunction with content area exams. It includes key points and critical thinking exercises (with answer keys) for nursing management for a variety of conditions.
"Building nursing knowledge to ensure NCLEX? success"--Cover.
Includes bibliographical references.
Keywords: Community health nursing -- Examinations, questions, etc; Nursing -- Examinations, questions, etc; Community Health Nursing; Public Health Nursing; Nursing--Outlines.; Nursing--Examinations, questions, etc